Successful Results of Intracytoplasmic Sperm Injection of a Chinese Patient With Multiple Morphological Abnormalities of Sperm Flagella Caused by a Novel Splicing Mutation in CFAP251 - Wang, Jiaxiong; Zhang, Ce; Tang, Hui; Zheng, Aiyan; Li, Hong; Yang, Shenmin; Xiang, Jingjing (Frontiers in Genetics, 2022)
Asthenospermia is one of the most important causes of male infertility. Among asthenospermia, multiple morphological abnormalities of sperm flagella (MMAF)are a relatively rare idiopathic condition which is mainly characterized by the multiple defects in sperm flagella.Although amount of studies focusing on genetic cause of MMAF had been reported, its pathogenesis and treatment effect remain largely unknown. Here,we reported a male patient from a non-consanguineous Chinese family who exhibited typical MMAF phenotype revealed by the morphological analysis. We identified a splicing mutations in CFAP251 (c.1192-3C>G) andthe mutation was proved to cause the exons skipping. Inaddition, western blotting andimmunofluorescence analysis of the spermatozoa from the proband and a control man revealed a significant lower expression of CFAP251 protein due to pathogenic mutations.Interestingly, his mother was a heterozygous carrier for the mutations but his father not, and finally the inheritance pattern was proved to bematernal uniparental disomy. We conducted the intracytoplasmic sperm injection and achieved a successful pregnancy. Above all, our findingshelp to expand the spectrum of CFAP251pathogenic mutation and give more reference to clinical genetic counseling and assisted reproductive treatment for such patients.